Disabled People Transforming Media Culture for a More Inclusive World - Haller, Beth A. (Routledge Research in Disability and Media Studies, 2024)
This book tells the stories of disabled people who have been influential in creating modern mass media. Through the voices of key disabled media makers and collaborators, the author highlights the ways in which their contributions are changing society's understanding of disability and shaping mass media and culture. Spanning a range of media formats - television/streaming productions, performances, podcasts, TED Talks, films, reality TV, graphic novels, and social media channels - the book illustrates how disabled people are confronting the marginalization they have faced in mass media for decades. Modern disabled media creators are leveraging new media platforms to recognize the lived experiences of disability and their authentic place in media culture. This innovative and thought-provoking volume will be an important read for scholars, disability advocates, and students of Disability Studies, Mass Communication/Media Studies, as well as mass media production faculty, disabled people, and their allies The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.